Deletion of CGLD1 Impairs PSII and Increases Singlet Oxygen Tolerance of Green Alga Chlamydomonas reinhardtii - Xing, Jiale; Liu, Peng; Zhao, Lei; Huang, Fang (Frontiers in Plant Science, 2017)
The green alga Chlamydomonas reinhardtii is a key model organism for studying photosynthesis and oxidative stress in unicellular eukaryotes. Using a forward genetics approach, we have identified and characterized a mutant x32, which lacks a predicted protein named CGLD1 (Conserved in Green Lineage and Diatom 1) in GreenCut2, under normal and stress conditions. We show that loss of CGLD1 resulted in minimal photoautotrophic growth and PSII activity in the organism. We observed reduced amount of PSII complex and core subunits in the x32 mutant based on blue-native (BN)/PAGE and immunoblot analysis. Moreover, x32 exhibited increased sensitivity to high-light stress and altered tolerance to different reactive oxygenic species (ROS) stress treatments, i.e. decreased resistance to H2O2/or tert-Butyl hydroperoxide (t-BOOH) and increased tolerance to neutral red (NR) and rose bengal (RB) that induce the formation of singlet oxygen, respectively. Further analysis via quantitative real-time PCR (qRT-PCR) indicated that the increased singlet-oxygen tolerance of x32 was largely correlated with up-regulated gene expression of glutathione-S-transferases (GST). The phenotypical and physiological implications revealed from our experiments highlight the important roles of CGLD1 in maintaining structure and function of PSII as well as in protection of Chlamydomonas under photo-oxidative stress conditions.